Comprehensive Physiology 2016
DOI: 10.1002/cphy.c150019
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Actions of Thyroid Hormone

Abstract: The hypermetabolic effects of thyroid hormones (THs), the major endocrine regulators of metabolic rate, are widely recognized. Although, the cellular mechanisms underlying these effects have been extensively investigated, much has yet to be learned about how TH regulates diverse cellular functions. THs have a profound impact on mitochondria, the organelles responsible for the majority of cellular energy production, and several studies have been devoted to understand the respective importance of the nuclear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 213 publications
2
59
0
Order By: Relevance
“…In contrast to our predictions, we did not observe clear context-dependent effects of THs on mtDNA copy number (hormone × heating, F1,155.8=0.55, p = 0.458, Fig 1d, Table S5), and also no apparent effect of prenatal TH elevation (F1,31.0=0.739, p=0.397, Table S5) or heating treatment (F1,41.5=0.003, p=0.958, Table S5) per se. While THs are known to affect mitochondrial biogenesis and function postnatally (25,26), only one previous study to our knowledge has investigated the effects of prenatal THs on mitochondrial parameters in a hypothyroid rat model. This study found no clear effects of prenatal THs on mitochondrial traits (28).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our predictions, we did not observe clear context-dependent effects of THs on mtDNA copy number (hormone × heating, F1,155.8=0.55, p = 0.458, Fig 1d, Table S5), and also no apparent effect of prenatal TH elevation (F1,31.0=0.739, p=0.397, Table S5) or heating treatment (F1,41.5=0.003, p=0.958, Table S5) per se. While THs are known to affect mitochondrial biogenesis and function postnatally (25,26), only one previous study to our knowledge has investigated the effects of prenatal THs on mitochondrial parameters in a hypothyroid rat model. This study found no clear effects of prenatal THs on mitochondrial traits (28).…”
Section: Resultsmentioning
confidence: 99%
“…Such metabolic changes are crucial for NSC fate commitment and differentiation . THs are major modulators of cell metabolism, and TH‐induced mitochondrial responses are directly implicated in stem cell differentiation . Here, we will discuss how changes in cell metabolism influence NSC commitment and differentiation, and how TH signalling impacts cell metabolism during neurogenesis.…”
Section: Implications Of Cell Metabolism On Neurogenesis and Th‐inducmentioning
confidence: 99%
“…In addition, THs are major modulators of cell metabolism, by affecting genomic and non‐genomic pathways regulating mitochondrial activity . NSC determination and differentiation also implicate metabolic shifts.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have reported the association between DM and TD [1][2][3][4][5], and evidenced a range of complex links between biochemical, genetic and hormonal malfunction sex planning their pathophysiological association [5][6][7]. In 1927, Coller and Huggins proved the association of hyperthyroidism and deterioration of diabetes and found that the subtotal thyroidectomy improves glucose tolerance in patients with hyperthyroidism with coexisting diabetes [8].…”
Section: Introductionmentioning
confidence: 99%